Inuit subsistence rights in Nunavik: A legal perspective of food security in the Artic - Otis, Ghislain; Thériault, Sophie (HAL CCSD, 2010)
Intervention dans le cadre du Forum 2010 LASCAUX - SPIDH. 13 pages. International audience This article outlines some of the key issues relating to the security of the subsistence rights of the Inuit in Nunavik. It is as part of a broader research question aimed at achieving a better understanding of how food security relates to legal security with regard to access to and use of country-food resources by Aboriginal people. Existing research underscores the importance of subsistence economies in the quest for sustainable development and food security in the Arctic. It also acknowledges the critical role played by Aboriginal land rights regimes in securing access to the land and its renewable resources. This article thus ascertains the legal foundations and scope of Inuit subsistence rights in Nunavik under the James Bay and Northern Quebec Agreement and the Nunavik Inuit Land Claims Agreement. It also briefly examines how these rights interact with other uses of the land and identifies potential insecurity-generating features of the Agreement's subsistence regime. Les travaux de recherche sous-estiment généralement l'importance des économies de subsistance dans la perspective du développement durable et de la sécurité alimentaire dans la région de l'Arctique. Ils méconnaissent également le rôle central des règles de droit aborigènes relatives au foncier, qui garantissent l'accès à la terre ainsi que le renouvellement des ressources naturelles. Non seulement ces règles méritent d'être examinées, mais un travail portant sur l'articulation entre ces dernières et d'autres sources juridiques reste à mener.